Transmission and Generation Expansion Planning Considering System Reliability and Line Maintenance - Mahdavi, Meisam [UNESP] (2018)
This study investigates the economic and reliability effects of line maintenance on composite transmission and generation expansion planning, considering the reliability of transmission and generation systems. The aim is to find a compromise among the expansion costs of the transmission and generation systems, power system reliability, and the maintenance cost of transmission lines. To do so, the reliability of the transmission system is modeled using load shedding (LS) due to line outages, and the reliability of the generation system is calculated using the loss of load (LOL) and LS criteria due to generating unit outages and transmission congestion. The proposed model was tested on the IEEE Reliability Test System (IEEE RTS). The paper includes a discussion of the results.